Halal logo and consumers' confidence: what are the important factors? - Mohamed, Zainal Abidin; Rezai, Golnaz; Shamsudin, Mad Nasir; Chiew, Eddie Fook Chong (Malaysian Agricultural Research and Development Institute (MARDI), 2008)
The food consumed by Muslims must meet the Islamic dietary code called Halal. Halal is an Arabic word meaning lawful or permitted. Muslim consumers are found to be very concerned about the Halalness of the foods they consume. The recent Halal food crises and its diffusion through the media in Malaysia had as consequence, in general, reduced public confidence, and of the Muslims in particular, in the products that they purchase. The lack of enforcement in the monitoring of the Halal food products has caused consumers to query the validity on the products or services claiming to be Halal. These public outcries have triggered the interest of researchers to study the level of confidence on the Halal food products and the logo which is associated with it. This paper aims to assess consumers’ confidence relating to Halal logo on food products and the factors that can help to enhance the level of confidence among the Muslim consumers in Malaysia. A total 600 respondents were interviewed via structured questionnaires to gather information on their level of confidence and purchasing behaviour towards food products with Halal logo. Factor analysis was used to determine the factors which influenced consumers’ confidence towards Halal food. The results indicate that socio-economic variables play an important role when explaining consumer behaviour. The underlying factors contributing to confidence are those related to safety and government involvement, as well as degree of awareness, trustworthy and manufacturing practice. These factors were found to be the major factors determining Malaysian consumers’ confidence on Halal logo of food products.